Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Penghasilan dalam APBN - Amin Isnanto; Istiqomah Istiqomah; Suharno Suharno (Universitas Batanghari Jambi, 2021)
The source of state revenue comes from taxes, the tax collected by tax collectors is then managed to become state expenditure for operational and development implementation of government and community affairs. One element of state income is the income tax. This study analyzes the relationship between state revenue, especially Income Tax, in the structure of the State Revenue Budget from several external factors such as inflation, the exchange rate of Indonesian rupiah (Rp.) to US dollar (US ), interest rates, and Indonesian crude oil price. From these factors, which one influences the growth of income tax revenue. The exchange rate of Indonesian rupiah (Rp.) to US dollar (US ) has a significant effect on income tax. Indonesian crude oil price, interest rates, and inflation have no effect on income taxes.